2006
DOI: 10.1002/app.24096
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and mechanical properties of poly(ethylene terephthalate)/lamellar zirconium phosphate nanocomposites

Abstract: ABSTRACT:The preparation of nanocomposites of poly (ethylene terephthalate) (PET) and lamellar zirconium phosphorous compounds by melt extrusion was investigated. Two types of zirconium phosphorous compounds were synthesized by the direct precipitation reaction method: a-zirconium bis(monohydrogen orthophosphate) monohydrate (ZrP) and organic-inorganic hybrid layered zirconium phenylphosphonate (ZrPP). Composites containing 2 and 5 wt % ZrP and ZrPP were prepared in a twin-screw extruder and specimens were obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 19 publications
0
34
0
Order By: Relevance
“…To improve the physical properties of PLA, especially in terms of thermomechanical stability, addition of different fillers (nanoparticles) in PLA was explored [2,[9][10][11]. Most of the literature regarding nanocomposites is devoted to lamellar layered silicates, in particular organically modified montmorillonites due to their ability to significantly enhance several polymer physical properties as compared to unmodified layered silicate clays, including gas barrier, flame retardancy, thermal stability and influence on the polymer biodegradation rate [2,[12][13][14]; however, needle like phyllosilicates (sepiolites) and zirconium phosphate are also reported in literature [15][16][17][18][19][20][21]. Sepiolite is a layered hydrated magnesium silicate characterized by a needle like morphology based on alternated blocks of tunnels in the fibre direction [16] and very high surface area (BET 374±7 m 2 /g) [23] as compared to layered phyllosilicates (BET 82±1 m 2 /g) [23,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To improve the physical properties of PLA, especially in terms of thermomechanical stability, addition of different fillers (nanoparticles) in PLA was explored [2,[9][10][11]. Most of the literature regarding nanocomposites is devoted to lamellar layered silicates, in particular organically modified montmorillonites due to their ability to significantly enhance several polymer physical properties as compared to unmodified layered silicate clays, including gas barrier, flame retardancy, thermal stability and influence on the polymer biodegradation rate [2,[12][13][14]; however, needle like phyllosilicates (sepiolites) and zirconium phosphate are also reported in literature [15][16][17][18][19][20][21]. Sepiolite is a layered hydrated magnesium silicate characterized by a needle like morphology based on alternated blocks of tunnels in the fibre direction [16] and very high surface area (BET 374±7 m 2 /g) [23] as compared to layered phyllosilicates (BET 82±1 m 2 /g) [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the few papers on PLA, Poly (#-caprolactone) (PCL), PP and Poly (butylene terephthalate) (PBT) [15,16], the possibility of an unmodified sepiolite to well disperse in polymers by melt blending was evidenced and mainly attributed to the large concentration of surface silanols, spaced every 0,5 nm along the length of sepiolite needle [30][31][32], that are easily available for coupling reactions with local polarity on polymer chains. Zirconium bis(monohydrogen orthophosphate) monohydrate, ($-Zr(HPO 4 ) 2 (H 2 O) ($-ZrP)), has a layered structure with many interesting properties, such as high density of grafted organic modifiers, high thermal stability [33], possible achievement of large aspect ratios, high elastic modulus and the potential to delaminate and become intercalated within the polymer [17,18]. PLA/zirconium phosphate composites has been studied and showed intumescent flame-retardant properties [34].…”
Section: Introductionmentioning
confidence: 99%
“…[20]. Zirconium bis(monohydrogen orthophosphate) monohydrate, (-Zr(HPO 4 ) 2 ·H 2 O) (-ZrP), is a layered structure material with many interesting features, such as high ion-exchange capacity, thermal and chemical stability [22], 3 catalytic activity, ionic conductivity, and the potential to delaminate and become intercalated within the polymer [23]. Many of these properties are common to natural layered nanofillers such as montmorillonite, but -ZrP has a higher ion exchange capacity [24], and has different elements in its structure.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these properties are common to natural layered nanofillers such as montmorillonite, but -ZrP has a higher ion exchange capacity [24], and has different elements in its structure. However, only a few studies have been reported on layered zirconium phosphate polymer nanocomposites, such as preparation of epoxy-α-ZrP [24][25][26][27] nanocomposites, polyethyleneimine-γ-ZrP nanocomposites [28] and poly (ethylene terephthalate)/lamellar zirconium phosphate nanocomposites [23]. Furthermore, the foci of these studies was the synthesis and the improvement of thermal or mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…The system was kept under agitation and reflux at 110 °C, for 24 hours. After that, the resulting material was centrifuged (3400 rpm for 30 min) and washed successively with deionized water in order to obtain neutral pH and absence of chloride [16][17][18] . The resulting solid was placed in a freezer at -80 °C for 24 hours and then submitted to lyophilization for 4 days.…”
Section: Synthesis Of Layered Zirconium Phosphatementioning
confidence: 99%